Schwannoma of the abdominal wall – diagnostic challenge - Nikolić, Bojan; Vukomanović Djurdjević, Biserka; Mitrović, Miroslav; Golubović, Jelena; Pešić, Jasna (Vojnosanitetski pregled, 2021)
Introduction. Schwannoma or neurilemmoma is a benign tumor of the nerve sheath originating from the Schwann cells. Localization in abdominal wall is rare. Schwannomas usually manifest themselves as slow-growing asymptomatic tumors. Symptomatology depends on the location, the involved nerve and the size of the tumor. Case report. We present a 43-year-old female patient with a schwannoma localized in the right hypochondriac region. Diagnostic procedures included ultrasound with color Doppler (US), high-resolution magnetic resonance imaging (MRI), and histopathological examinations (HP). US showed a solid, well-circumscribed mass, with a whorled, echogenic internal architecture in the anterior abdominal wall. MRI revealed an oval, well-circumscribed, heterogeneous, 3 × 2.5 × 2.5 centimeters large fusiform mass. T1-weighted imaging presented low signal intensity, while T2-weighted image showed heterogeneously high signal intensity. The lesion was completely removed. After pathohistological analysis with standard and immunohistochemical methods of coloring, the diagnosis of the schwannoma was confirmed. Conclusion. Schwannoma as a slow-growing tumor, which is often without clinical manifestations, may cause a delay in diagnosis and treatment. Clinical presentation of a schwannoma is indolent and non-specific. Diagnosis of this tumor requires a multidisciplinary and interdisciplinary approach. MR is a useful and highly specific method for the verification of peripheral nerve sheath tumors. A HP analysis confirmed definitive diagnosis of the lesion.